The spectrum of congenital heart defects in neonates of diabetic mothers - Sharifi, Abdul; Ekram, Khesrow; Wali, Wali (Universitas Airlangga, 2023)
Introduction: Insulin-dependent diabetes mellitus (IDDM) in a mother is considered a risk factor for congenital malformation, including congenital heart diseases. Many studies signify a five to six times increased frequency of congenital heart diseases in neonates born from insulin-dependent diabetic mothers. This study aimed to identify the spectrum of congenital heart diseases (CHDs) in neonates born from insulin-dependent diabetes mellitus (IDDM) mothers. Methods: Between April 2019 and March 2021, a descriptive cross-sectional study involved 120 consecutive neonates aged 0-28 days of mothers with insulin-dependent diabetes mellitus (IDDM) at Maiwand Teaching Hospital, Kabul University of Medical Sciences. Neonates born to non-diabetic mothers were excluded. IDDM refers to mothers using Insulin upon admission to control blood glucose. CHD encompasses various heart defects affecting function. Family and maternal history were noted, focusing on health issues and delivery details. Neonatal mothers' ages ranged from 23 to 45 (mean 33), with diabetes onset spanning 2.5 to 25 years. Pediatric cardiologists conducted physical and echocardiographic exams. All CHD forms were documented using 2D echocardiography and Doppler studies (Sono Ace X-6 Machine). Result: 120 consecutive neonates born to mothers with insulin-dependent diabetes mellitus (IDDMs) were investigated during the two-year study period. Of them, 18 (15%) had congenital heart abnormalities. The prevalence of solitary and multiple CHD was 66.6 percent (12 patients) and 33.3 percent (6 patients) in the 18 infants born from IDDMs. The most prevalent isolated defects were PDA (22.2%) and Ventricular septal defect (16.6%). The most common multiple CHDs (16.6 percent) were PDA and ASD. PDA + ASD (16.6%) and VSD + PDA were the most frequent correlations with CHD (11.1 percent). Conclusion: Maternal insulin-dependent diabetes mellitus is an important risk factor for congenital heart disease. Careful assessment and early diagnosis of CHD in this high-risk group are very important in a pediatric population. Expansion of prenatal screening programs for CHDs in mothers suffering from insulin-dependent diabetes mellitus is necessary. Keywords: congenital heart diseases; diabetic mothers; insulin dependent; neonates